(untitled) (CAHIERS MAGELLANES-NS, 2024)
A vital area of medical research where people are still working to find a better solution is bone tissue regeneration particularly when it comes to healing fractures, abnormalities, or degenerative one disorders. Recent research has stated that tissue engineering can be a better treatment methodology for this problem because it is a combination of cell biology, material science and research which has brought a lot of significant changes in material science that produces new tissues which resemble the native one. Tissue engineering involves growing stem cells or fabricating biomimetic scaffolds that facilitate the new bone formation which increases the life of a human being. In recent years the advancement in this treatment is producing synthetic biomaterials which is a combination of metal particles incorporated into the scaffolds. In that way conjugates of Gracilaria-strontium–chitosan that stimulates both bone growth and inhibits bone resorption. Gracilaria is chosen because it is highly tolerated by the living tissues due to its biocompatibility. The dimensional structure displayed by the Gracilaria helps in cells to multiply and differentiate which is important during the new bone formation to provide a supporting framework. Strontium helps in replacing the calcium ions at the site of hydroxyapatite crystal lattice as it is comparable to calcium in size and charge. Chitosan is a naturally occurring source that is biodegradable and that increase the activity of osteoblast that promotes osteogenesis. The results state that the combination of the algae, chitosan and the strontium particles enhances the expression level of the genes responsible for the osteogenic differentiation. This paper presents the results of fabrication and characterization of the scaffold, In vitro evaluation of biocompatibility properties of the scaffold and In vivo assessment of the scaffold for bone formation.